Grid-connected lithium-ion battery energy storage system: A bibliometric analysis for emerging future directions - Wali S.B.; Hannan M.A.; Ker P.J.; Rahman M.A.; Mansor M.; Muttaqi K.M.; Mahlia T.M.I.; Begum R.A. (Elsevier Ltd, 2023)
Digital storage; Energy efficiency; Energy storage; Ions; Sustainable development; 'current; Battery energy storage systems; Bibliometrics analysis; Grid; Grid-connected; Keyword search; Lithium ions; Research and development; Research impacts; Research trends; Lithium-ion batteries